Kant's Understanding of the Enlightenment with Reference to his Refutation of Materialism - Rumore, Paola (Con-Textos Kantianos. International Journal of Philosophy, 2014)
The paper focuses on the role of Kant’s refutation of materialism in his understanding of the Enlightenment, meant to be the necessary condition that allows human beings to express their proper dignity, i.e. to cultivate the urge for and the vocation of free thought. Sketching the main moments of the German struggle against the threat of materialism, the paper places Kant’s refutation within this tradition, and reconstructs the steps of his critique from the very beginning of his reflection – still dealing with the main topics of Wolff’s metaphysic – up to the definitive refutation he develops on the basis of the transcendental idealism of the first Critique. The shift from the «obscure reasons» pointed out in the Dreams, that allow a refutation of materialism on moral grounds, to the statement of the meaninglessness of the question in a transcendental perspective reveals that the attempt to find a solution to the problem of materialism – most of all in its psychological meaning –represents a neverending challenge within Kant’s reflection.